Ischemic hypoxic encephalopathy: The role of MRI of neonatal injury and medico-legal implication. (October 2021) - Midiri, Federico; La Spina, Corinne; Alongi, Alberto; Vernuccio, Federica; Longo, Marcello; Argo, Antonina; Midiri, Massimo
Abstract: Hypoxic ischemic encephalopathy is one of the major causes of neonatal death and neurological disability in the child, and represents the most common birth injury claim. Intrapartum asphyxia often leads to several long-term sequalae, such as cerebral palsy and/or developmental delay, epilepsy. Through the neuroimaging it's possible to identify and define the different lesioned pictures and provide useful elements to establish the moment in which the damage occurred; indeed, timing of injury is a key element in the legal arena. Magnetic resonance imaging (MRI) is emerging as one of the most important tools in identifying the etiologic of neonatal encephalopathy as well as in predicting long-term outcomes. The aim of this study is to evaluate all MRI tests performed in a group of infants and young patients with possible neonatal encephalopathy, in order to determine the role of MRI in perinatal hypoxic-ischemic damage and the specific patterns that can point towards a diagnosis of the time of the damage's onset. Another goal is to assess the role of MRI in cases subject to legal-medical ligation. Since the advent of hypothermic neuroprotection, new malpractice allegations have arisen, including the failure to initiate cooling in a timely manner. In all cases, documentation of the status of the baby at birth, including a thorough neurologic exam, can be extremely helpful to the later defence of a malpractice claim, which might occur years later.